Growth is dead, long live growth: The quality of economic growth and why it matters - Haddad, Lawrence; Kato, Hiroshi; Meisel, Nicolas (Japan International Cooperation Agency, 2015)
What growth do we mean by the most desirable development? How can we advance the growth for achieving its aims? The JICA Research Institute has been conducting joint research on the quality of growth since 2012 in collaboration with the French Development Agency (AFD) and the Institute of Development Studies (IDS) . The book is the outcome of a series of joint research activities.